The river between - Ngugi wa Thiongo, 1938- (London : Heinemann, 1965)
'Explores life on the Makuyu and Kameno ridges of Kenya in the early days of white settlement. Faced with an alluring new religion and'magical' customs, the Gikuyu people are torn between those who fear the unknown and those who see beyond it. Some follow Joshua and his fiery brand of Christianity. Others proudly pursue tribal independence. In the midst of this disunity stands Waiyaki, a dedicated visionary born to a line of prophets. He struggles to educate the tribe--a task he sees as the only unifying link between the two factions--but his plans for the future raise issue which will determine both his and the Gikuyu's survival'--back cover.
Keywords: Kikuyu (African people) -- Kenya -- Fiction; Kenya -- History -- 1895-1963 -- Fiction